Who wins wars? - Jonathan-Julian Federle; Dominic Rohner; Moritz Schularick (Kiel Institute for the World Economy (IfW Kiel), 2025)
Economic resources are often seen as decisive for the outcomes of military conflicts. This paper asks whether "deeper pockets" help win wars. We construct a fine-grained dataset covering more than 700 interstate disputes and rely on exogenous resource price shocks to estimate the causal effect of windfall gains on winning chances in interstate conflicts. We find a statistically significant and quantitatively large impact of windfall gains on winning odds and show that a key channel of transmission is a surge in military spending, after an exogenous increase in government revenues.
Keywords: D74; F51; H56; N40; Q02; 330; Interstate disputes; International wars; Commodity prices; Conflict outcomes; Military expenditures